Implementation of the Remuneration System on the Level of Job Satisfaction of Nurses in Hospitals - Putra, Erdiansyah; Oktamianti, Puput (Jurnal Health Sains, 2025)
Nurse job satisfaction is critical for healthcare quality, yet existing research often narrowly focuses on remuneration without considering its interplay with organizational culture, leadership, and post-pandemic demands. This study examines how pay systems interact with non-financial factors to influence nurse satisfaction, aiming to identify context-specific strategies for hospitals. A narrative review analyzed 10 years of literature from PubMed, ScienceDirect, and EBSCOhost using keywords like "remuneration," "nurse satisfaction," and "hospital compensation." Competitive wages boost morale and retention, but holistic satisfaction requires supportive leadership, career growth opportunities, and mental health support. Gaps persist in qualitative insights and regional adaptability. Hospitals should adopt flexible, data-driven pay models aligned with nurses' needs, while future research must employ mixed methods and cross-regional comparisons to refine policies.